An Investigation of the Early Involvement of Facilities-Management Specialists into the Traditional Design-Development Process: the Causes of Conflicts - Cruywagen, J.H.H. (University of Pretoria, 2021)
Dissertation (MEng)--University of Pretoria, 2020.